Surveillance of the physical, chemical, and microbiological quality of swimming pool water in the Hamadan province - Mostafa Leili (Journal of Advances in Environmental Health Research, 2017)
Swimming is considered one of the most conventional recreational activities for both leisure and exercising. Swimming pools have either public or private usage. Nevertheless, if the water of the swimming pools is polluted and is not identified on time, it could result in the transmission of various diseases to the people who use them. Therefore, the main objective of this study was to assess the health situation of swimming pools in the Hamadan province during the period of 2012–2014.This research was a descriptive-analytical (cross-sectional) study on the 19 active pools in the 8 cities of Hamadan province. A total of 120 samples were randomly taken from different parts of the swimming pools during the three-year study period. The sampling and testing procedures were performed according to standard methods. The SPSS software (IBMÒ) and the linear correlation test were used for data analysis. The results showed that the physicochemical parameters, such as pH and residual chlorine for 76% and 86% of the total samples, respectively, showed good compliance in pool water during the study period. In terms of microbiological parameters, the lowest and highest numbers of positive samples were observed in the years 2012 and 2014, respectively. According to the results and the unfavorable trend observed mainly in terms of microbial contamination, appropriate measures, such as through strict enforcement of sanitary standards and provision of required equipment like turbidity meter, should be undertaken in order to increase the hygiene level of swimming pools in the Hamadan province.